Association between Duffy blood group system variants and susceptibility and resistance to malaria in the Brazilian Amazon - Weber, Simone Schneider; Tadei, Wanderli Pedro; Martins, Adriana Sotero (Revista de Biologia Neotropical / Journal of Neotropical Biology, 2011)
The interaction between Duffy blood group proteins and Plasmodium vivax is necessary for the establishment of the erythrocytic phase of malaria, because these molecules act as receptors for the protozoan. This study showed significant associations between Duffy blood group variants and susceptibility and resistance to vivax malaria. In the present study, Duffy blood group genotyping and phenotyping were carried out for 244 individuals living in a Brazilian area where malaria is endemic and P. vivax identification was performed by thick blood smears. Our results showed that 80 individuals were positive and 164 were negative to P. vivax. We registered a high frequency of genotype FYAFYB (47.5%), followed by FYBFY (15.6%), FYAFYA (14.3%), FYBFYB (11.5%), FYAFY (8.6%), and FYFY (2.5%). The frequencies of FYA, FYB, and FY alleles were 55%, 38.8%, and 6.3% in infected individuals, respectively, whereas in non-infected ones they were 36.3%, 45.1%, and 18.6%, respectively. These results demonstrate that FYA allele is more frequent in individuals infected with vivax malaria. The null genotype was not found in infected subjects, but was present in 3.7% of the non-infected individuals. We also found 11.5% discordance between genotype and phenotype. The estimated genetic frequency proved that the population participating in the study did not show genetic balance according to Hardy-Weinberg.